2015
DOI: 10.1144/sp420.11
|View full text |Cite
|
Sign up to set email alerts
|

Magma imaged magnetotellurically beneath an active and an inactive magmatic segment in Afar, Ethiopia

Abstract: This paper presents broadband magnetotelluric data collected along profiles over two magmatic segments comprising part of the subaerial Red Sea arm of the Afar triple junction. One of these segments has been active since late 2005 and the other segment is currently inactive. After robust processing and galvanic distortion analysis, we found that the data passed the twodimensional subsurface resistivity modelling criteria. Profiles across the segments had welldefined geoelectrical strike directions parallel to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
25
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(26 citation statements)
references
References 73 publications
0
25
1
Order By: Relevance
“…From the dimensionality analysis and very small tipper values, we conclude that there are no indicators for off-profile conductors in the data, so we consider the absence of a conductive anomaly at the proposed depth of the magma chamber as a robust feature in our model and not an MT resolution issue. This is in stark contrast to the situation elsewhere in the MER and Afar, where the presence of magma is associated with an electrically conducting subsurface (e.g., Didana et al, 2015;Johnson et al, 2015;Whaler & Hautot, 2006). This first order contradiction between our MT results and other geophysical and geochemical observations gives new insights into the storage of melt under an on-axis volcano in the CMER.…”
Section: Melt Storage Under Alutocontrasting
confidence: 96%
See 1 more Smart Citation
“…From the dimensionality analysis and very small tipper values, we conclude that there are no indicators for off-profile conductors in the data, so we consider the absence of a conductive anomaly at the proposed depth of the magma chamber as a robust feature in our model and not an MT resolution issue. This is in stark contrast to the situation elsewhere in the MER and Afar, where the presence of magma is associated with an electrically conducting subsurface (e.g., Didana et al, 2015;Johnson et al, 2015;Whaler & Hautot, 2006). This first order contradiction between our MT results and other geophysical and geochemical observations gives new insights into the storage of melt under an on-axis volcano in the CMER.…”
Section: Melt Storage Under Alutocontrasting
confidence: 96%
“…Previous surveys have highlighted the capability of MT to quantify the amount of magma present in the subsurface. Desissa et al () and Johnson et al () estimated magma volumes below the Manda‐Hararo magmatic segment in Afar based on the observation of very high conductivities using models that link electrical conductivity to melt fractions. Further south in the Main Ethiopian Rift, Whaler and Hautot () found that the subsurface was significantly less conductive than in Afar but that there were still conductive features located below the rift axis as well as near the rift flanks.…”
Section: Introductionmentioning
confidence: 99%
“…This is most clearly evident at the Dabbahu and Hararo magmatic segments, the location of the 2005–2010 Dabbahu dyking event (Ebinger et al, ; Grandin et al, ; Illsley‐Kemp et al, ). Previous studies also find slow velocities (Korostelev et al, ; Stork et al, ) and high conductivities (Desissa et al, ; Johnson et al, ), which have been used to estimate a 500‐km 3 melt body with 13% melt beneath this region associated with the dyking event (Desissa et al, ). Slow velocities coupled with the recent dyking event suggest we image melt associated with the event.…”
Section: Discussionmentioning
confidence: 96%
“…Again, many different disciplines have been applied, including petrology and geochronology (Ferguson 2011;Ferguson et al 2013a;Field et al 2013;Medynski et al 2013Medynski et al , 2015, magnetotellurics (Desissa et al 2013;Johnson et al 2015), seismology Hammond & Kendall 2016), geodesy (Grandin et al 2010a;Pagli et al 2012) and combinations of techniques (Field et al 2012). Collectively, these studies show that the Afar crust contains large quantities of partial melt and they give insights into how it is stored.…”
Section: The Dabbahu Rifting Episode and The Afar Rift Consortiummentioning
confidence: 99%
“…This book includes seven studies that document different aspects of magmadominated rifting in Afar. Johnson et al (2015) used broadband magnetotelluric observations to compare the conductivity structure beneath the active Dabbahu segment of the Arabia -Nubia plate boundary with that beneath the currently inactive Hararo segment. As the dominant cause of high conductivity anomalies below the shallow crust is melt, they used these observations to quantify the amount of melt present beneath each rift segment.…”
Section: Magma-dominated Rifting In the Afar Triple Junctionmentioning
confidence: 99%